A Systematic Review of Pedagogical Models to Enhance Students’ Critical Thinking in Physics Learning - Rasyid, Muhammad; Unayah, Habibatul; Kuswanto, Heru; Aminatun, Tien; Sulistiyawati, Sulistiyawati; Bog, Kim Jung (Jurnal Pendidikan MIPA, 2024)
Critical thinking skills are important skills needed in the 21st century  Critical thinking skills can be trained in students through student-centered learning  This research aims to identify learning models that can improve physics critical thinking skills through a literature review  Data collection is based on Scopus and SINTA database sources  This type of document comes from magazine articles tagged "critical thinking", "learning models", "physics learning" for the year (2019-2024)  Methods adapted from PRISMA were used for the literature search  Published documents are based on predetermined content analysis criteria, such as year of publication, author, article source, learning model, physical material topic, research topic, education level, and evaluation  Inquiry learning and higher order thinking laboratories (HOT Labs) are the dominant learning models used to improve critical thinking skills  The main competency indicators used vary  Indicator of critical thinking abilities  Self-regulated learning is rarely used in research tools compared to other indicators of critical thinking abilities  The instruments used are multiple choice questions, essays, worksheets and observation sheets  University-level research participants often use critical thinking skills in their research  Fluid mechanics is a popular topic in research  This research will help improve students' critical thinking skills through various recommended learning models  Research shows that student-centered learning models can improve critical thinking skills.        Keywords: critical thinking skills, fluid mechanics, guided inquiry, learning models, physics learning.DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1444-1467